Transformation of Maslahah Principles in E-Commerce in Al - Ghazali's View - Daredmi, Salsabilla; Rozalinda; Zulvianti, Nora (SAFE-Network, 2024)
This study explores the application of the principle of maslahah as formulated by Al-Ghazali in the context of e-commerce in Indonesia, particularly regarding Sharia-compliant online loans (pinjol) that grew significantly during 2022-2023. The study analyzes this phenomenon through the lens of maslahah, focusing on the protection of wealth (hifz al-mal) and honor (hifz al-‘ird). The results indicate that although Sharia-compliant fintech provides broader financial access, unethical practices such as high returns (0.1% per day or 36% annually) and aggressive debt collection methods contradict consumer protection principles. A lack of transparency in contracts and data breaches further threaten core maslahah values. The study recommends stricter regulations from the OJK and DSN-MUI and improving Sharia financial literacy to ensure a balance between technological innovation, Sharia compliance, and consumer protection. In conclusion, Al-Ghazali's maslahah principles remain relevant and must be adapted to address e-commerce challenges in the digital era.